Iceland and China: Strategic Partnership in the Arctic and Euro-Atlantic - Kirill V. Babaev (Современная Европа)
The article analyses the development of China-Iceland relations which led to a full-scale political and economic partnership between the two countries, the current issues in Chinese policies towards Iceland, its plans to use the island as a starting point for expansion in Europe, Atlantic and Arctic regions. The paper explores the interests of the two states, stages of development of their relations, recent development with China’s return to Iceland after three years of the pandemic, and Chinese intentions to enhance the partnership in order to extend its influence in Arctics and Euro-Atlantics. This analysis sheds light on the Chinese policy in the Arctic which is important for the future of Russo-Chinese relations in the region, and on how the Chinese entrenchment in Northern Europe may change the balance of power and interest not only in the Arctic, but in the Euro-Atlantic region. The article reveals that China, as a non-Arctic state, is striving to intensify cooperation with Iceland, but the relations in recent years have begun to sour both due to the pressure from the United States and the EU, as well as pandemic restrictions. Despite Iceland's tense relations with the European partners and the United States and the active assistance of China, in the future Iceland may be inclined to choose the United States as a strategic partner.